2007
DOI: 10.1021/la0610396
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Tethered Bilayer Lipid Membranes on Gold Surfaces:  QCM-Z and AFM Study

Abstract: Recently, tethered bilayer lipid membranes (tBLMs) have shown high potential as biomimetic systems due to their high stability and electrical properties, and have been used in applications ranging from membrane protein incorporation to biosensors. However, the kinetics of their formation remains largely uninvestigated. By using quartz crystal microbalance with impedance analysis (QCM-Z), we were able to monitor both the kinetics and viscoelastic properties of tether adsorption and vesicle fusion. Formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
2
33
1
Order By: Relevance
“…The results obtained in this study are quite different to those published by Dorvel et al 32 They showed a biphasic kinetic curve for the adsorption and reorganization of the DPhyTL into a self-assembled monolayer. The QCM monitoring of DPhyTL deposition at 300 M ͑ϳ1 ϫ 10 −4 mg/ ml͒ on gold showed a linear frequency shift, which reached Ϫ15 Hz after 5 h, followed by a stronger frequency decrease from 8 to 21 h until a plateau at a frequency shift of ⌬f ϳ −50 Hz was reached.…”
Section: Monolayer Assemblycontrasting
confidence: 99%
See 1 more Smart Citation
“…The results obtained in this study are quite different to those published by Dorvel et al 32 They showed a biphasic kinetic curve for the adsorption and reorganization of the DPhyTL into a self-assembled monolayer. The QCM monitoring of DPhyTL deposition at 300 M ͑ϳ1 ϫ 10 −4 mg/ ml͒ on gold showed a linear frequency shift, which reached Ϫ15 Hz after 5 h, followed by a stronger frequency decrease from 8 to 21 h until a plateau at a frequency shift of ⌬f ϳ −50 Hz was reached.…”
Section: Monolayer Assemblycontrasting
confidence: 99%
“…Dorvel et al reported on the fusion of anchorlipid vesicles in the formation of the monolayer, which is not very probable, since the lipids are completely soluble in ethanol. 32 Furthermore, the combination of electrical and optical techniques offers more insight into the processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several sensing platforms that are capable of hosting transmembrane proteins within BLM based devices have been proposed, including: patch clamp arrays (Mathes, 2006;Dale et al, 2007;Lau et al, 2006;Wee-Liat Ong et al, 2007;Li et al, 2006;Fertig et al, 2003), patterns of tethered BLMs (Taylor et al, 2007;Han et al, Orth et al, 2003;Andersson et al, 2007;Dorvel et al, 2007;Pera and Fritz, 2007), BLMs formed by deposition of giant unilamellar vesicles over micro-and nano-pores (Mach et al, 2008;Schimdt et al, 2000) and arrays of BLMs, both suspended and hydrogelsupported (Maurer et al, 2007;Castellana and Cremer, 2006;Le Pioufle et al, 2008;Suzuki et al, 2004;Wilk et al, 2007;Baaken et al, 2008). Each of these platforms offer both advantages and disadvantages: for instance, tethered bilayers allow for geometrical patterning of analysis sites, similar to protein printing technology, but the membrane fluidity, and consequently the conformational structure of any reconstituted ion channels, can be altered (Deverall et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…
Solid supported lipid membranes provide a simple biomimetic model system that is suitable for studying a wide range of membrane related phenomena and importantly permits the use of a number of surface analytical techniques [1][2][3][4][5][6][7][8] from AFM to impedance spectroscopy to be used in characterising such processes. Additionally, it is also believed that such systems could find application for drug screening, biosensing or in protein separation/crystallisation.
…”
mentioning
confidence: 99%